Lithophagy Prolongs Voluntary Dives in American alligators (Alligator mississippiensis). Issue 1 (2nd January 2019) - Uriona, T J; Lyon, M; Farmer, C G
Abstract: Many vertebrates ingest stones, but the function of this behavior is not fully understood. We tested the hypothesis that lithophagy increases the duration of voluntary dives in juvenile American alligators ( Alligator mississippiensis ). After ingestion of granite stones equivalent to 2.5% of body weight, the average duration of dives increased by 88% and the maximum duration increased by 117%. These data are consistent with the hypothesis that gastroliths serve to increase specific gravity, and that the animals compensate by increasing lung volume, thereby diving with larger stores of pulmonary oxygen.